3D Pose and Curvature Estimation of Bendable Interventional Device using Single-view X-ray Image - Sunghwan Lim; Junhyoung Ha; Lee, Deukhee (42ND ANNUAL INTERNATIONAL CONFERENCES OF THE IEEE ENGINEERING IN MEDICINE AND BIOLOGY SOCIETY: ENABLING INNOVATIVE TECHNOLOGIES FOR GLOBAL HEALTHCARE EMBC'20, 2020)
We present a novel method to estimate the 3D pose and curvature of bendable interventional devices using a single X-ray image. A preliminary experiment was performed to demonstrate the feasibility of the proposed method. The mean estimation accuracies were 3.48mm and 0.59mm for the 3D pose and the radius of curvature of the bendable cardiac ablation catheter, respectively. This method has the potential to help clinicians to make a better intraoperative decision during the procedure, resulting in expedite surgery and reduce exposure to ionizing radiation.
Keywords: Catheter tracking; Computer assisted intervention; Curvature estimation